Projeto e desenvolvimento de um sistema de gerenciamento remoto sem fio aplicado a iluminação - Vargas, Diogo Ribeiro (2012)
Today's light sources are expanding the application field of lighting systems for decorative, commercial and artistic purposes, in many areas, such as parks, gardens or parking. This paper presents the development of a management system applied to lighting based on power RGB LEDs, due to its great potential for use in outdoor decorative lighting. The proposed system is a low cost solution and presents the advantage of remote management of the lighting system on multiple interfaces, either on a dedicated device, as for portable devices, such as laptops, smartphones or tablets. After an analysis of currently lighting systems protocols, it is also proposed a new communication protocol for the developed system in order to get a reliable and robust solution. This work also presents the results of the proposed system, highlighting its main advantages and limitations.